Intertextuality in the Short-Short Stories: The Case of Ahmed Jarallah Yassin - Mohammed Saeed Hassan, Raghad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The study of Intertextuality in the short-short stories (flash fiction) of Ahmed Jarallah Yassin reveals the writer’s profound awareness of both Arab and international narrative heritage, as well as his ability to re-employ it within a modern artistic framework. Intertextuality in his works is not confined to quotation or citation; rather, it goes beyond that to create new semantic and aesthetic relationships, thereby enriching the dimensions of the text and opening it to multiple artistic contexts. The narrative structure of his short-short stories also incorporates vivid visual scenes, which he skillfully crafts, reflecting his tendency to experiment with a tool not easily integrated into the structural plot of this genre. Such writing relies on maximum linguistic brevity and compression to construct stories distinguished by a different method, vision, and uniqueness of expression. Accordingly, this critical study aims to explore the functions of intertextuality in Yassin’s short-short stories. Yassin , a critic, short story writer, and poet, is distinguished by his personal imprint and unique style in literary writing. Intertextuality stands out as a striking feature in his narratives, carrying deep meanings and connotations that engage with reality through depiction, critique, and irony. DOI: https://doi.org/10.54633/2333-024-056-014